If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f * 4 + 5 = 11 Reorder the terms for easier multiplication: 4f + 5 = 11 Reorder the terms: 5 + 4f = 11 Solving 5 + 4f = 11 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4f = 11 + -5 Combine like terms: 5 + -5 = 0 0 + 4f = 11 + -5 4f = 11 + -5 Combine like terms: 11 + -5 = 6 4f = 6 Divide each side by '4'. f = 1.5 Simplifying f = 1.5
| .25x=1567.50 | | (a+3)(a+3)=0 | | 3cos^2(x)-5cos(x)=2 | | -u/u^2 | | x-7(2x-3)=2(5x-2)-3(4x+9) | | (36y^2)-5=y-18y^2 | | -2+3(x-4)=3x-9(x-3)-1 | | 7(x-8)+9=5(x-7) | | 4x-2y=800 | | 5x+3-1*2=54 | | 7(x+6)+x=4(4x+4)+6 | | 2a+7=25+8 | | .417/.875 | | 3x-2(3x-2)=6-(3x-8)+9x | | 7(x-3)+x=2(x+5)+2 | | X^2+x-2=x^3 | | 5/12/7/8 | | (-4+7i)(1+i)= | | 4(2x+5)-(8x+5)=15 | | (3x^4)/(6)=x^6/30 | | 12x/15x | | -(6-3*6)-5=-2*6-2*6+1solve | | X^7=x^4+65 | | .2(4z-10)=.8z-2 | | 1/5(4z-10=4/5z-2 | | (2-v)(2v-3)=0 | | -4(x-4)+5=6(x+4)+1 | | 2x+2X+x=940 | | 5(-6x+9)+7= | | 20x+10=60w | | 10x=5(6x-2) | | -6(5x+7)+9= |